Targeted delivery of microRNA 146b mimic to hepatocytes by lactosylated PDMAEMA nanoparticles for the treatment of NAFLD. (5th November 2018) - He, Shuying; Guo, Weihong; Deng, Feihong; Chen, Kequan; Jiang, Yonghong; Dong, Minyu; Peng, Liang; Chen, Xueqing
Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases worldwide, and precision therapeutic will be a benefit for the NAFLD regression. In this study, we observed low microRNA 146 b (miR-146 b) expression in NAFLD mice model induced by methionine–choline-deficient diet (MCD) compared with control group. Furthermore, miR-146b −/− mice induced MCD exhibited severe liver steatosis and hepatitis. A bio-distribution study showed that novel Lactosylated PDMAEMA nanoparticles effectively targeted hepatocytes Lac-PDMAEMA. We coupled miR-146b mimic with Lac-PDMAEMA and then were administrated to NAFLD mice model, which could obviously alleviate the hepatic steatosis. Lac-PDMAEMA effectively delivered miR-146b mimic to hepatocytes with a ∼8-fold upregulation of miR-146b mimic targeting MyD88 and IRAK1, and in turn suppressed the expression of PPARγ. Meanwhile, TNF-α and IL-6 mRNA levels were decreased after administration of Lac-PDMAEMA/miR-146b mimic. So, we made a conclusion that targeted delivering miR-146b mimic to the hepatocytes by, coupling Lac-PDMAEMA nanoparticles could effectively alleviate the hepatic steatosis in NAFLD mice, which maybe bring a new and effective way to intervene and therapy the NAFLD. Graphical Abstract: